FM14 Session 1: Bridging the Astronomy Research and Outreach Communities - Recent Highlights, Emerging Collaborations, Best Practices and Support Structures. Issue Volume 14:Issue A30(2018) (August 2018) - Cheung, Sze-leung; Vauclair, Sylvie D.; Cui, Chenzhou; Li, Shanshan; Hanaoka, Yoichiro; Hunt, Sharon E.; Kawagoe, Shio K.; Kusakabe, Nobuhiko; Nakamura, Shigeru; Maravelias, Grigoris; Vourliotis, Emmanouel; Marouda, Krinio; et al.
Abstract: Section 1 of the FM14 focus on bridging the astronomy research and outreach communities - recent highlights, emerging collaborations, best practices and support structures. This paper also contains supplementary materials that point to contributed talks and poster presentations that can be found online.